Rio 2016 : Olympic myths, hard realities - Zimbalist, Andrew S. (Knowledge Unlatched Select 2017 (on order), 2017)
"Rio 2016 assembles the views of leading experts on Brazil and the Olympics into a clear-eyed assessment of the impact of the games on Brazil in general and on the lives of Cariocas, as Rio's residents are known"--Publisher's website